Kebijakan Hutang, Kebijakan Dividen, Dan Profitabilitas, Serta Dampaknya Terhadap Investment Opportunity Set (IOS) - Andita Novianti; Nicodemus Simu (Jurnal Manajemen Teori dan Terapan | Journal of Theory and Applied Management, 2016)
This research aimed to analyze the impact of the debt policy, dividend policy, and the profitability of each proxied by DER, DPR and ROE thru the investment opportunity set with CAPBVA as the proxy. The population of this research is a trade service company, services and investments which are listed on the Stock Exchange. The sampling method used is purposive sampling, 19 companies are selected as research objects with 76 samples of data involved. Data analysis technique is used multiple linear regression analysis. The analytical tool used to process data is E-Views 8.0. The results of this research showed that the DER and DPR has a significant negative effect on IOS, while ROE has no significant effect on IOS. The influence proportion of the independent variables can explain IOS by 16.38 percent, while 83.62 percent is explained by other variables outside the research model.